Behavior of the First Variation of Fourier Transform of a Measure on the Fourier Feynman Transform and Convolution. (2nd June 2016) - Kim, Young Sik
ABSTRACT: We investigate the behavior of a first variation of a Fourier transform of a measure of the form : upon the Fourier-Feynman transform and analytic Feynman integral and the convolution, where and { h 1, h 2, …, h n } is the orthonormal class of elements in H on the abstract Wiener space ( H, B, m ).